2011
DOI: 10.1007/s10120-011-0071-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the accuracy and utility of peritoneal cytology in patients with gastric cancer

Abstract: Background There is lack of uniformity in the utilization of peritoneal cytology in gastric cancer management. The identification of intraperitoneal free cancer cells (IFCCs) is believed to confer poor prognosis. However, while some of these patients are palliated, others may undergo more aggressive therapies. In this review, we aimed to identify and synthesize findings on the use of peritoneal cytology in predicting peritoneal recurrence and overall survival in curative gastric cancer patients. Methods Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 51 publications
2
67
1
1
Order By: Relevance
“…The use of RT-PCR to detect micrometastatic disease is currently not widely accepted because of its variation in technique, the choice of detection of different tumor-derived antigens, and the possibility of false-positive results. In fact, a recent systematic review incorporating a number of studies that examined the utility of RT-PCR showed wide confidence intervals in diagnostic performance, including an accuracy of 61-89.7 %, sensitivity of 31-100 %, and specificity of 58.8-95 % [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of RT-PCR to detect micrometastatic disease is currently not widely accepted because of its variation in technique, the choice of detection of different tumor-derived antigens, and the possibility of false-positive results. In fact, a recent systematic review incorporating a number of studies that examined the utility of RT-PCR showed wide confidence intervals in diagnostic performance, including an accuracy of 61-89.7 %, sensitivity of 31-100 %, and specificity of 58.8-95 % [2].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) is used selectively in patients with early-stage tumors to determine if endoscopic resection is feasible or whether neoadjuvant therapy is warranted. Laparoscopy and peritoneal cytology have been shown to detect occult metastatic disease not seen on conventional imaging [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Patients with cancer cells in the peri-toneal cavity (peritoneal cytology positive; CY1) could constitute such a population. A CY1 status is a predictor of peritoneal dissemination 4 and a poor prognostic factor in patients with gastric cancer. [5][6][7][8] However, the recent introduction of chemotherapy has changed the clinical picture to some extent.…”
mentioning
confidence: 99%